The Relationship between Mastery Experience and Teacher Self-Efficacy:A Meta-Analytic Review - Nordin, Mohamad Sahari; Halim, Lilia; Ibrahim, Mohd Burhan; Libdeh, Enas (IIUM Press, 2017)
Despite the potency of teacher self-efficacy, not much is known about what makes a teacher efficacious. Hence, this meta-analysis took to the task of examining the likelihood and magnitude of the relationship between mastery experience and teacher self-efficacy, and identify moderators of the association. A total of 39 original studies involving 9,560 teachers were examined. The respondents were teachers of various school levels, and 15 of the studies involved both primary and secondary school teachers. Almost two thirds of the primary studies were conducted in Western settings, while the rest were Asian studies. To identify the moderators, the study applied a meta-regression procedure. The results supported the expectation that mastery experience positively influences teacher self-efficacy. Additionally, it was discovered that differences in research design, school level, and culture impacted the variability of the relationship. Studies that employed experimental designs produced marked effects on the relationship. An interesting finding was that culture moderated the relationship between mastery experience and teacher self-efficacy where Western teachers were found to exhibited superior teacher self-efficacy than their Asian counterparts.